SAT0683 A north-south worldwide gradient in systemic activity of primary sjÖgren syndrome: increased severe disease in patients from southern countries. (12th June 2018) - Retamozo, S.; Acar-Denizli, N.; Fai Ng, W.; Zeher, M.; Rasmussen, A.; Seror, R.; Li, X.; Baldini, C.; Gottenberg, J.-E.; Danda, D.; Quartuccio, L.; Priori, R.; et al.
Abstract : Objectives: To analyse the influence of geolocation on the clinical systemic presentation of primary Sjögren syndrome (SjS) at diagnosis. Methods: The Big Data Sjögren Project Consortium is an international, multicentre registry created in 2014. Centres were classified by continent, with an additional north-south sub-classification according to latitude (>or<50'N in Europe, equator >or or<30'N in Asia). Systemic involvement at diagnosis was retrospectively scored using the ESSDAI. Results: The highest baseline ESSDAI scores were reported from Southern vs Northern countries in Europe (7.2 vs 4.6, p<0.001), America (5.3 vs 3.5, p<0.001) and Asia (6.3 vs 3.9, p<0.001). In Europe, the frequency of activity in each domain was higher in Southern countries (in all domains except constitutional, p<0.001). In America, Southern countries had the highest frequencies of active patients in constitutional, articular, cutaneous, pulmonary, PNS and CNS domains (p<0.001 in all) and the lowest frequencies in lymphadenopathy (p=0.018) and biological (p<0.001) domains. In Asia, patients from China had the highest frequency of activity in glandular, articular, pulmonary, muscular, haematological and biological and those from India in lymphadenopathy, cutaneous, renal and PNS. Conclusions: This study provides the first evidence for a strong influence of geolocation on the systemic phenotype of primary SjS at diagnosis. Geographical determinants should be considered as key variables when systemic disease is scored. Disclosure of Interest: None declared